2019
DOI: 10.1155/2019/2457854
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Explosive Separation of Pyrotechnic Cutter

Abstract: Pyrotechnic cutters are widely used in the wrapping-band connecting structures of carrier rockets. In this article, a three-dimensional (3D) finite element model of a pyrotechnic cutter is proposed to determine the influence of the explosive dynamic fracture process and the cutter blade acceleration distance on the cutting effect, using AUTODYN finite element simulation software. Numerical simulations of the cutting process reveal that the initial shear speed, the maximal speed, and the speed at which the cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…pressure gas in the propulsion system in space missions, and has the characteristics of safety, simplicity and reliability. A pyrotechnic cutter is widely used in the belt connection structure, and Xiong et al [5] established a finite element simulation model of the cutter to provide help for the design optimization of the cutter and the study of its action mechanism. In addition, Han et al [6] carried out a systematic study on the design and optimization of a PAD, established a model to analyze the sensitivity of the design parameters, and improved the working performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…pressure gas in the propulsion system in space missions, and has the characteristics of safety, simplicity and reliability. A pyrotechnic cutter is widely used in the belt connection structure, and Xiong et al [5] established a finite element simulation model of the cutter to provide help for the design optimization of the cutter and the study of its action mechanism. In addition, Han et al [6] carried out a systematic study on the design and optimization of a PAD, established a model to analyze the sensitivity of the design parameters, and improved the working performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…[6] used exible energy-gathering cutting cables to cut carbon ber composites, analyzed and discussed the phenomenon of composite delamination, and concluded that the strength and thickness of the plate have an impact on the delamination effect. Xiong et al [7] designed a three-dimensional (3D) nite element model of pyrotechnic cutters by using AUTODYN nite element simulation software and studied the in uence of explosion dynamic fracture process and blade acceleration distance on cutting effect. Yao [8] studied the working principle and separation characteristics of the explosive separation device through numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Hsiao [3] studied the characteristics of shaped charge jets using the finite element method. Xiong et al [4] designed a three-dimensional (3D) finite element model of pyrotechnic cutters by using AUTODYN finite element simulation software and studied the influence of explosion dynamic fracture process and blade acceleration distance on cutting effect. Takeuchi [5] simulates the separation and fracture process of the spacecraft according to the shock response.…”
Section: Introductionmentioning
confidence: 99%